Public health and regulation in the management of human corpses in private funeral homes in Yucatán, Mexico - Tinoco, Itzel Rubi Díaz; Cime, Luis Fernando Castañeda (Seven Editora, 2024)
Objective: To analyze the problem of disposing of human corpses in private funeral homes in the state of Yucatán, Mexico. Materials and Methods: The study is based on the use of Legal Research Methodology through the analysis of the legal framework and institutional provisions that concern the treatment of human corpses. Results: It was found that the process of preparing and embalming human corpses is complex, due to the cultural burden present in the country and, therefore, in the different states of the Mexican Republic, where death has a deeply rooted space in social understanding. The process of preparing the body, in addition, contains a wide spectrum of derived problems, which involve other social actors, which are often not considered, but which go beyond the personnel who handle the bodies in hospitals or the Legal Medical Service. We are talking about private funeral service providers in charge of preparing bodies to carry out funeral ritual processes before burial or cremation. DOI:https://doi.org/10.56238/sevened2024.010-025